2016
DOI: 10.1080/03003930.2016.1263188
|View full text |Cite
|
Sign up to set email alerts
|

Helpful local surtaxes? Florida and disadvantaged families

Abstract: Well-intended tax policy often produces unintended consequences. In this article, we look at one such tax policy, specialised surtaxes in the State of Florida. Surtaxes are frequently adopted to provide financial assistance to poverty-based local programmes and services. Despite the intended benefits, we show that the contributors of the tax have been able to capitalise the cost into the residential property market, ultimately placing the burden of the surtax upon the population its revenue intends to help.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Although renters are exempt from paying property taxes on the houses they rent, and thus unlikely to focus on the size of the tax levy, Yinger et al (1988) have shown that the burden of a property tax may be transferred to renters. This transference is the result of property owners increasing the rental costs of the property to compensate for the imposed tax (see also Eger et al, 2017). Although renters may prefer lower taxes to higher ones, the saliency of the tax burden creates a false sense of security.…”
Section: Theory and Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Although renters are exempt from paying property taxes on the houses they rent, and thus unlikely to focus on the size of the tax levy, Yinger et al (1988) have shown that the burden of a property tax may be transferred to renters. This transference is the result of property owners increasing the rental costs of the property to compensate for the imposed tax (see also Eger et al, 2017). Although renters may prefer lower taxes to higher ones, the saliency of the tax burden creates a false sense of security.…”
Section: Theory and Backgroundmentioning
confidence: 99%
“…Since Tiebout's (1956) research on public expenditures, the public finance literature has assumed that people are rational actors. Based on this rationality, people seek to maximize their income by minimizing their tax burden (see also Burman, 2013; Eger et al, 2017). Over time, the expectation of rationality, and its implication of a preference for lower taxes, has become commonplace in the literature.…”
Section: Theory and Backgroundmentioning
confidence: 99%
See 1 more Smart Citation